(untitled) (Research, Society and Development, 2025)
Microhepathy is characterized by a reduction in the functional mass of the liver and can be caused by several factors. Among them is portosystemic shunt, which can be congenital or acquired. Blood draining from the stomach, intestine, and spleen is diverted from the liver, preventing the detoxification of substances and carrying them into the systemic circulation, increasing pre- and postprandial serum bile acid levels, as well as ammonia concentrations. This study reports a case of microhepathy in a mixed-breed dog (MSB), secondary to portosystemic shunt. The patient presented with clinical signs of weight loss, vomiting, erratic appetite, and neurological signs, such as wandering. The diagnosis was established based on laboratory tests for serum cholesterol levels, pre- and postprandial serum bile acid levels, and ultrasound. Treatment was instituted with dietary changes, specific food for patients with liver disease, and supplementation with nutraceuticals, probiotics, and omega-3. This report highlights the possibility of stabilizing the clinical condition of a patient with portosystemic shunt through diets when surgical correction is not possible.